Advances in Plant Defense Mechanisms - Ngui Kimatu, Josphert (IntechOpen, 2022)
Increasing human migrations, technological advances, agricultural activities, and climate change are forcing plants to adapt to new environments. This book highlights current morphological, anatomical, physiological, molecular, and genomic advances in plant defense mechanisms. These advances, including epigenetic mechanisms, have been linked to observed phenotypic plant plasticity. The book also outlines next-generation food systems, considering the resilience and sustainability of plant genomes and epigenomes.